1996
DOI: 10.1177/074193259601700503
|View full text |Cite
|
Sign up to set email alerts
|

School-Linked Services Integration

Abstract: This article considers the implications of the school-linked services integration reform movement for professional practice and discourse in the fields of special and remedial education, as well as for the broader political goal of democratic transformation in america. although we see the services integration policy agenda as an important vehicle for addressing a variety of interrelated social and educational problems associated with the transition to a postmodern society, we argue that it hasn't been adequate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Two studies on links between multicultural urban schools and their communities in Sweden (Bouakaz, 2007;Bunar, 2001) found that educators indeed tended to divide the concept of school community into two separate components and treated them in different ways. On the one hand, there was what Skrtic and Sailor (1996) call school-linked service integration, that is, the level and quality of cooperation with governmental and municipal services and authorities deployed in the neighborhood such as police, welfare officers, health care, and youth workers. Even civic organizations outside the neighborhood, such as universities and businesses (Benton, Zath, & Hensley, 1996), were considered a part of this wider community component.…”
Section: School-linked Service and Civil Society Integrationmentioning
confidence: 99%
See 1 more Smart Citation
“…Two studies on links between multicultural urban schools and their communities in Sweden (Bouakaz, 2007;Bunar, 2001) found that educators indeed tended to divide the concept of school community into two separate components and treated them in different ways. On the one hand, there was what Skrtic and Sailor (1996) call school-linked service integration, that is, the level and quality of cooperation with governmental and municipal services and authorities deployed in the neighborhood such as police, welfare officers, health care, and youth workers. Even civic organizations outside the neighborhood, such as universities and businesses (Benton, Zath, & Hensley, 1996), were considered a part of this wider community component.…”
Section: School-linked Service and Civil Society Integrationmentioning
confidence: 99%
“…Parents and ethnic and religious associations represented the other component of the school community that Skrtic and Sailor (1996) labeled as school-linked civil society integration. Relationships with these groups were often strained and pervaded by suspicion, low expectations, and even stigmatization.…”
Section: School-linked Service and Civil Society Integrationmentioning
confidence: 99%
“…Systems integration theory emerged in the 1990s as a progressive agenda to cut across encapsulated service systems to achieve a seamless web of educational, health, welfare, and community services matched to individual need, regardless of the cause of that need (e.g., disability, poverty), and provided as a kind of "wraparound" system (Adelman & Taylor, 1998;Haines & Turnbull, 2013;Halverson & Sailor, 1990;Skrtic & Sailor, 1996;Tyack, 1992;Zollers, 2002). Systems integration theory, also described as services integration, was defined by Gerry (2002) as a set of stereotypes by which a community seeks to ensure the immediate and uninterrupted access of all children and families to those children's services and family supports needed by the family to optimize the cognitive, social, emotional, and physical development of each of its children, and to ensure the healthy functioning, stability, social, and economic self sufficiency both of the family and the neighborhood of which it is a part.…”
Section: Systems Integration Theorymentioning
confidence: 99%
“… 8.For discussion on the so-called community school, see Arum (2000); Ascher (1988); Epstein (1995); Sanders (2003); Skrtic and Sailor (1996). …”
mentioning
confidence: 99%